Effect of activation of nuclear factor-KappaB on modulation of secretion of intercellular adhesion molecule-1 by A549 cell - Liao, Pin-hu (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2009)
OBJECTIVE: To investigate the effects of interleukin-1beta (IL-1beta) on intercellular adhesion molecule-1 (ICAM-1) expression on A549 cell and underlying signal transduction pathways